Tinjauan yuridis penerapan sanksi tindak pidana perzinahan dalam perspektif Undang-Undang No. 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana [Juridical review of the application of sanctions for the criminal act of adultery from the perspective of Law No. 1 of 2023 concerning the Criminal Code] - Wardana, Zarmendi Irsan; Rosikhu, Muhammad; Efendi, Saparudin (Indonesia Berdaya, 2025)
Zina merupakan perbuatan yang termasuk perbuatan yang termasuk dalam konotasi negatif atau dilarang. Dalam skripsi ini memiliki tujuan Untuk menganalisa pengaturan tindak pidana perzinahan dalam Undang-undang No. 1 Tahun 2023 Tentang Kitab Undang-undang Hukum Pidana. Selanjutnya untuk menganalisa bagaimana rumusan sanksi tindak pidana perzinahan dalam perspektif Undang-Undang No. 1 Tahun 2023 Tentang Kitab Undang-undang Hukum Pidana. Penelitian ini menggunakan metode hukum Normatif. Rumusan tindak pidana perzinahan bisa dijatuhkan pidana kerja sosial dimana sanksi pidana perzinahan yaitu penjara paling lama 1 (tahun) atau denda paling banyak kategori II. Tindak pidana perzinahan juga bisa diselesaikan dengan cara restoratif juctice dilakukan dengan mediasi penal dan dialog antar pelaku, korban dan pihak terkait. Abstract. Adultery is an act that includes negative connotations or is prohibited. This thesis aims to determine the regulation of the crime of adultery in Law no. 1 of 2023 concerning the Criminal Code. Next, to find out how the sanctions for the crime of adultery are formulated from the perspective of Law no. 1 of 2023 concerning the Criminal Code. IThis study uses the Normative law method. The results of this thesis show that the formulation of the crime of adultery can be subject to social work where the criminal sanction for adultery is a maximum of 1 (year) imprisonment or a maximum fine of category II. The crime of adultery can also be resolved by means of restorative justice carried out through penal mediation and dialogue between the perpetrator, victim and related parties.